Dual T/NK cell engagement via B7-H6-targeted bispecific antibodies and IL-15 eradicates chemo-resistant solid tumors - Ma, Xuqian; He, Huixia; Zhu, Yuankui; Zuo, Dianbao; Wang, FangLin; Feng, Mingqian; Ji, Kangkang; Chen, Xin (Frontiers in Immunology, 2025)
IntroductionB7-H6, a tumor-specific immune checkpoint molecule within the B7 family, represents a promising therapeutic target due to its selective overexpression in malignancies and negligible expression in normal tissues.MethodHere, we developed bispecific antibodies (BsAbs) targeting B7-H6 to redirect T and NK cells against solid tumors. Through phage display, 15 high-affinity B7-H6 monoclonal antibodies were generated.ResultsTwo optimized BsAbs, B7-H6M4-OKT3 (T cell-engaging) and B7-H6M4-LC21 (NK cell-engaging), were constructed in and scFv-hFc-scFv format. Both demonstrated nanomolar affinity (EC50: 0.04–1.22 nM) and selective cytotoxicity against B7-H6+ cells (H446, Huh-7, HepG2), while showing minimal cytotoxicity against B7-H6-negative cells (A431). B7-H6M4LC21 exhibited enhanced tumor-killing efficacy (IC50: 5 ng/mL) compared to B7H6M4-OKT3(IC50: 1 ng/mL) when combined with an IL-15/IL-15Ra sushi fusion protein, which augmented NK cell proliferation and cytotoxicity. In H446 xenograft models, both BsAbs suppressed tumor growth in a dose-dependent manner (0.1–20 mg/kg) without significant toxicity. Combination therapy with B7-H6M4-LC21 (10 mg/kg) and B7-H6M18/IL-15/IL-15Ra sushi (0.03 mg/kg) achieved synergistic tumor inhibition (p<0.05), surpassing the efficacy of T cell-based combinations.DiscussionThese findings establish B7-H6-targeted BsAbs combined with cytokine engineering as a viable strategy for treating refractory solid tumors.